Occurrence and traceability of Listeria monocytogenes strains isolated from sheep's milk cheese-making plants environment. (January 2015) - Spanu, Carlo; Scarano, Christian; Ibba, Michela; Spanu, Vincenzo; De Santis, Enrico Pietro Luigi
Abstract: The aim of the study was to conduct an extensive survey on Listeria monocytogenes and Listeria spp. environmental contamination in 13 cheese-making plants. A total of 409 environmental and food samples were collected during years 2011–2013. Listeria spp. contamination was observed in all the facilities, while L. monocytogenes was recovered from 12 facilities with a prevalence ranging between 3.0% and 22.6%. Floor drains were the most contaminated sampling sites (48.8% of positive samples), serving as harbourage site for subsequent contamination. Out of 616 isolates, 277 (45.0%) were Listeria innocua, 274 (44.5%) L. monocytogenes, 41 (6.6%) Listeria ivanovii, 14 (2.3%) Listeria welshimeri and 10 (1.6%) Listeria gravyi . Serotyping carried out by PCR and agglutination method for L. monocytogenes revealed that 169 strains (61.7%) were serotype 1/2a, 65 (23.7%) 4b, 20 (7.3%) 1/2b, 10 (3.6%) 3a, 7 (2.5%) 1/2c and 3 (1.1%) 3b. PFGE conducted on L. monocytogenes isolates using Asc I and Apa I restriction enzymes, yielded 6 clusters. Two predominant PFGE clusters were observed including respectively 36 and 32 strains. Within cheese-making plants, L. monocytogenes showed wide variability with strains distributed up to 4 different clusters. Pulsotypes isolated from raw milk filter were never detected in the processing environment, indicating that the contamination originated from sources other than raw milk. The isolation of strains with similar profile from different sampling sites, within and among cheese-making plants, indicated the possible transfer of L. monocytogenes contamination along production lines and from one facility to another. Strains recovered from food were confirmed as originating from the processing environment. Highlights: Molecular characterization of Listeria monocytogenes isolated from cheese-making plants. Traceability of L. monocytogenes contamination in food and processing environment. Genetic variability of L. monocytogenes among and within cheese-making plants.